Phenolic Bioactives From Plant-Based Foods for Glycemic Control - Sarkar, Dipayan; Christopher, Ashish; Shetty, Kalidas (Frontiers in Endocrinology, 2022)
Plant-based foods containing phenolic bioactives have human health protective functions relevant for combating diet and lifestyle-influenced chronic diseases, including type 2 diabetes (T2D). The molecular structural features of dietary phenolic bioactives allow antioxidant functions relevant for countering chronic oxidative stress-induced metabolic breakdown commonly associated with T2D. In addition to antioxidant properties, phenolic bioactives of diverse plant foods have therapeutic functional activities such as improving insulin sensitivity, reducing hepatic glucose output, inhibiting activity of key carbohydrate digestive enzymes, and modulating absorption of glucose in the bloodstream, thereby subsequently improving post-prandial glycemic control. These therapeutic functional properties have direct implications and benefits in the dietary management of T2D. Therefore, plant-based foods that are rich in phenolic bioactives are excellent dietary sources of therapeutic targets to improve overall glycemic control by managing chronic hyperglycemia and chronic oxidative stress, which are major contributing factors to T2D pathogenesis. However, in studies with diverse array of plant-based foods, concentration and composition of phenolic bioactives and their glycemic control relevant bioactivity can vary widely between different plant species, plant parts, and among different varieties/genotypes due to the different environmental and growing conditions, post-harvest storage, and food processing steps. This has allowed advances in innovative strategies to screen and optimize whole and processed plant derived foods and their ingredients based on their phenolic bioactive linked antioxidant and anti-hyperglycemic properties for their effective integration into T2D focused dietary solutions. In this review, different pre-harvest and post-harvest strategies and factors that influence phenolic bioactive-linked antioxidant and anti-hyperglycemic properties in diverse plant derived foods and derivation of extracts with therapeutic potential are highlighted and discussed. Additionally, novel bioprocessing strategies to enhance bioavailability and bioactivity of phenolics in plant-derived foods targeting optimum glycemic control and associated T2D therapeutic benefits are also advanced.